Device simulation and experimental validation of perovskite-cadmium telluride 4T tandem solar cell - Menon, Harigovind; Yan, Feng (Frontiers in Energy Research, 2024)
Developing tandem solar cells is an excellent strategy to break through the Shockley-Queisser (SQ) limit for single-junction solar cells. A major factor in developing a tandem solar cell is to make it cost-efficient with high device performance. Here, we demonstrate the proof of concept of four terminal (4T) tandem solar cell using a perovskite solar cell (PSC) as a wide bandgap (WBG) top cell and narrow bandgap (NBG) cadmium telluride (CdTe) as a bottom cell. A 4T tandem device power conversion efficiency (PCE) exceeding 23% was obtained using SCAPS (solar cell capacitance simulator) simulation, demonstrating the architecture's feasibility. Further, we fabricated two WBG semitransparent perovskite cells with different bandgaps (1.6eV and 1.77eV) and mechanically stacked it with NBG CdTe (1.5eV) to obtain tandem efficiencies of 18.2% and 19.4% respectively. From the results, we concluded that the PSC with a bandgap of 1.77eV is more suitable to be paired with the NBG CdTe solar cell to get good device performance and effective